Lack of GNAQ and GNA11 Germ-Line Mutations in Familial Melanoma Pedigrees with Uveal Melanoma or Blue Nevi - Hawkes, Jason E.; Campbell, Jennifer; Garvin, Daniel; Cannon Albright, Lisa; Cassidy, Pamela; Leachman, Sancy A. (Frontiers in Oncology, 2013)
Approximately 10% of melanoma cases are familial, but only 25-40% of familial melanoma cases can be attributed to germ-line mutations in the CDKN2A - the most significant high-risk melanoma susceptibility locus identified to date. The pathogenic mutation(s) in most of the remaining familial melanoma pedigrees have not yet been identified. The most common mutations in nevi and sporadic melanoma are found in BRAF and NRAS, both of which result in constitutive activation of the MAPK pathway. However, these mutations are not found in uveal melanomas or the intradermal melanocytic proliferations known as blue nevi. Rather, multiple studies report a strong association between these lesions and somatic mutations in Guanine nucleotide-binding protein G(q) subunit alpha (GNAQ), Guanine nucleotide-binding protein G(q) subunit alpha-11 (GNA11) and BRCA1 associated protein-1 (BAP1). Recently, germ-line mutations in BAP1, the gene encoding a tumor suppressing deubiquitinating enzyme, have been associated with predisposition to a variety of cancers including uveal melanoma, but no studies have examined the association of germ-line mutations in GNAQ and GNA11 with uveal melanoma and blue nevi. We have now done so by sequencing exon 5 of both of these genes in 13 unique familial melanoma pedigrees, members of which have had either uveal or cutaneous melanoma and/or blue nevi. Germ-line DNA from a total of 22 individuals was used for sequencing; however no deleterious mutations were detected. Nevertheless, such candidate gene studies and the discovery of novel germ-line mutations associated with an increased MM susceptibility can lead to a better understanding of the pathways involved in melanocyte transformation, formulation of risk assessment, and the development of specific drug therapies.